AUGMENTED REALITY BERBASIS ANDROID UNTUK PENGENALAN PERALATAN LABORATORIUM - Arya Wiratama, I Kadek; Care Khrisne, Duman; Sudarma, Made (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i01.p13, 2018)
To gift a chance to students, lab learning is a learning process that supervised practical application with practical tools of a previously studied theory. Lack of lab clerk and time, causing lack of understanding of using tools when practical process. This study aims to assist the introduction phase of practicum tools, with Augmented reality technology, built on unity3D, Vuforia and blender with marker in the form of Augmented reality Book (AR book). From test refound that marker detection at best performance when marker is build at A4 paper size with color information and maximum of 3 closed marker area. Testing with System Usability Scale tested by Electrical Engineering Study Program students got best score at statement point 1,7 and 9